PENGUATAN STRATEGI PEMASARAN MENGGUNAKAN PLATFPROM DIGITAL BERBASIS ARTIFICIAL INTELLEGENCE (AI) PADA UMKM INDUSTRI KREATIF DI KELURAHAN TELADAN KECAMATAN TOBOALI - Reniati, Reniati; Nizarudin, Abu; Bahri, Alim (Jurnal Abdi Insani, 2024)
Creative Industry MSMEs (Ikraf) have a very strategic role in the digital era economy. The digital literacy of Ikraf MSME actors is currently still low. Especially related to the ability to use Artificial Intelligence (AI) technology which is increasingly playing a role in business, especially to strengthen their marketing strategies so that they are able to Go Digital and Go Export. This program aims to improve the competence of both knowledge, skills and attitude  in utilizing Artificial Intelligence in the marketing strategies of Ikraf MSME actors in Teladan Village, Toboali District, South Bangka Regency. This service is in collaboration with Teladan Village which has 15 Ikraf MSMEs that have the potential to move up a class. The implementation of this activity is still ongoing from March 15, 2024 to October 15, 2024. The implementation of community service activities is carried out by conducting surveys, providing materials related to digital literacy and the use of AI and export opportunities. Furthermore, mentoring and Training are also carried out.